Field Trial Testing of an Electricity-Producing Portable Biomass Cooking Stove in Rural Malawi - Robinson, Anthony; O'Shaughnessy, Seamus (My University, 2014)
A novel off - grid electricity - producing device has been designed for integration with biomass - fuelled improved cooking stoves commonly in use in the developing world. The device operates on the thermoelectric principle whereby small amounts of electricity can be produced in response to a temperature difference across a thermoelectric generator, or TEG. The energy produced by the integrated g enerator can be used for direct charging or stored in a rechargeable lithium - iron - phosphate (LiFePo 4 ) battery. The generator is equipped with a standard USB output which allows the user to charge a variety of 5 Volt appliances. Five technology demonstrator electricity generating stoves have been integrated with locally produced clay cooking stoves in the Balaka district of Malawi, Africa. This study details the results from an 80 - day field trial of the devices. The data reveals that the stoves are in use fo r a greater time than was anticipated. The data also indicates that the generators perform adequately in the field and provide the user with the ability to charge LED lights and mobile phones from the generator stoves every day if necessary.
PUBLISHED
Keywords: Phone Charging; Lighting; Electricity Generation; Thermoelectric; Cook stove; Biomass; International Development; Smart & Sustainable Planet